Organizational culture and educational quality in university students - Mosqueira Cueva, Edgar Dino (2025)
Public universities face increasingly demanding, complex and changing environments. A response from university management is related to building an organizational culture that generates trust and has an impact on its members accepting institutional values ​​and goals, as well as identifying, getting involved and actively participating in their achievement, mainly in improving educational quality of the students; hence, this study aimed to assess whether organizational culture has a significant correlation with educational quality in a study program of a public higher education institution in Peru. It considered a quantitative methodological approach, basic type, observational design, transectional section and correlational descriptive scope. 128 students were surveyed using two questionnaires. The statistical correlation determined that, p- valor < ,05,which indicates a statistically significant relationship and a Rho = ,638 which indicates a correlation in a positive direction with medium strength. Therefore, it was evident that organizational culture and educational quality are correlated; When the organizational culture improves, educational quality will tend to improve and vice versa, in the studied study program.